PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBER HEADS TOGETHERS (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 10 BENGKALIS - Ema Dahlia; Syahrilfuddin Syahrilfuddin; Lazim. N Lazim. N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is motivated by the low science learning outcomes fourth grade students of SD Negeri 10 Bengkalis. The purpose of this research is to improve science learning outcomes fourth grade students of SD Negeri 10 Bengkalis. The number of subjects in this study is 28 people. The results showed that the application of learning models Number Heads Together (NHT) can increase the activity of teachers and students and also students' science learning outcomes. At the first meeting of the first cycle, teacher activity categorized simply by percentage of 54.17%. the second meeting, the activities of teachers are categorized either be 66.67%. At the first meeting of the second cycle, the activities of teachers percentage to 83.33% and categorized very well, and increased to 95.83% in the second meeting of the second cycle, with very good category. At the first meeting of the first cycle, the percentage of student activity amounted to 45.83% with less category. At the next meeting, increased to 66.67% and well categorized. In the second cycle, the first meeting of student activity categorized as good with a percentage of 79.17%. While the second meeting increased to 91.67% and categorized very well. Before action is taken, the average student learning outcomes at 60,25. in the first cycle, the average student learning outcomes increased to 70.89. Has been an increase amounted to 13.42%. In the second cycle, the average student learning outcomes increased to 83.21. Has been an increase amounted to 33.14%.Keyword: Learning models Number Heads Together (NHT), Science Learning Outcomes.